The Influence of Big Five Personality on Lecturer's Performance in Private University, Malaysia - Alawiyah Tengah; Abdul Rahim Zumrah (Faculty of Management & Muamalah, International Islamic University College Selangor, 2024)
Vol. 12. No. 2 (November 2022)